On the identity of Pselaphodes walkeri (Sharp, 1892) (Coleoptera: Staphylinidae: Pselaphinae), with description of a new related species - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2013)
The identity of Pselaphodes walkeri (Sharp, 1892) is clarified based on examinations of the holotype and recently collect-ed material from the type locality (Damao Island, Zhoushan Archipelago). Previous records of P. walkeri from West Tian-mushan Mountain (Zhejiang), Baishanzu Natural Reserve (Zhejiang) and Wuyishan Mountain (Jiangxi) are proven to be based on misidentifications, populations there represent a new species closely related to P. walkeri. Both P. walkeri and the new species are redescribed/described, illustrated and distinguished from the other members of the genus.